POPULATION EVALUATION OF THE EXPLOTABLE STOCK OF THE OPISTHONEMA COMPLEX (PISCES: CLUPEIDAE) IN THE GULF OF NICOYA, COSTA RICA - Vega-Corrales, Luis A. (Revista Ciencias Marinas y Costeras, 2010)
The Opisthonema genus supports the sardine fishery in Costa Rica. This research was directed to population assessment of the exploitable stock of this fishery in the Golfo of Nicoya. Monthly samples were collected since June, 2007 until May, 2008. The reproductive pattern of O. libertate were determined and growth parameters of curves in the length of O. libertate and O. medirastre were estimated using the von Bertalanffy model.. Based on the gonadosomatic index, O. libertate spawn intensively during the hottest time of the year, between February and May. The size at first maturity (SFM50%) was 18.68 cm T.L. The growth equation of von Bertalanffy was estimated for O. libertate: Tl= 25.9 [1–exp–1.03(t+0.13)] and O. medirastre: Tl= 32.0 [1–exp–1.10(t+0.15)]. The maximum recruitment to the fishery of O. libertate occurs between September and November. This species show an exploitation index (E) of 0.65 and O. medirastre have an E value of 0.55. It is note an improvement in the E value, as compared to previous values. It is recommended as management measure to adjust the close season, and to avoid any increment of the fishing effort.